Confronting Co-workers: Role Models, Attitudes, Expectations, and Perceived Behavioral Control as Predictors of Employee Voice in the Military - Hilverda, Femke; van Gils, Rick; de Graaff, Miriam Carla (Frontiers in Psychology, 2018)
Speaking up and confronting co-workers when they behave undesirably is important for the well-being of the personnel and organizational performance. In some organizations, a culture of silence prevails, however. Although a number of organizational environments are particularly receptive to employee voice, others are less open to voice behavior, which gives rise to a risk of undesirable behavior. Direct communication (voice) can reduce this enhanced risk. In this study, we used the Theory of Planned Behavior to examine the extent to which attitude, social norm and perceived behavioral control determine voice in hierarchical contexts, which, in general, tend to inhibit voice behavior. For this purpose, a survey study was conducted among military and civilian personnel of the Netherlands Ministry of Defense (n=374). Results showed that employee voice is rather high, regardless of rank, position or gender. Structural equation modelling showed that voice was significantly predicted by perceived behavioral control and injunctive norms (i.e. what is considered to be normal in a certain working-environment). Contrary to expectations, voice was not predicted by attitude and descriptive social norms (i.e. what people see that others are doing in this respect). Stimulating ‘confronting’ skills and creating a climate in which speaking up is perceived as normal may be beneficial for organizations in general and hierarchical organizations in particular.